RADIATION DOSE FROM NATURAL AND MANMADE RADIONUCLIDES IN THE SOIL OF NIAB, FAISALABAD, PAKISTAN - Akhtar, N.; Tufail, M.; Choudhry, M. A.; Orfi, S. D.; Waqas, M. (The Nucleus, 2020)
Natural Radioactivity originates from extraterrestrial sources as well as from radioactive elements in the earthâ€™s crust. The amount of radioactivity in soil varies widely and is a source of continuous exposure to human beings. Amount of radioactivity in soil depends upon the type of soil and its uses. For the investigation of amount of radioactivity in the fertile soil, an area of about 100 hectares of land was selected in NIAB (Nuclear Institute for Agriculture and Biology) at Faisalabad, Pakistan. Soil samples were collected from the cultivated and fertilized land. Activity concentration was measured using a HPGe (high purity germanium) ï§ ray detector and a PC based MCA. Specific activity levels due to 40K, 137Cs, 226Ra and 232Th were determined in 125 fertilized soil samples collected at a spacing of about 4 hectares at the depth level of 0â€“25 cm with a step of 5 cm depth. Activity concentration of the concerned radionuclides for the NIAB soil is: 40K, 614.4ï€670.7 Bqkg-1; 137Cs, 2.1ï€3.1 Bqkg-1; 226Ra, 28.6ï€32.6 Bqkg-1; and 232Th, 51.6ï€60.3 Bqkg-1. Chemical analysis for concentration of Na, Ca and Mg was also carried out along with the measurement of electrical conductivity and pH of the soil samples. The absorbed dose in air at NIAB Farm is 75 nGyh-1 which is higher than the world average of 57 nGyh-1 but lies within the range (18-93) nGyh-1.